Sustainable investing through exchange-traded products : exchange-traded funds and exchange-traded notes - Marszk, Adam (Routledge, 2026)
"Despite the rapid and substantial increase in the popularity of exchange-traded products (ETPs), particularly exchange-traded funds (ETFs), some categories remain underexplored in the academic and professional literature. One of the most notable examples is ETNs. This book offers a detailed yet highly focused insight into the exchange-traded notes (ETNs) market. The book presents the key attributes and mechanisms of ETNs, such as their number, providers, assets, listing locations, benchmarks, charges and objectives, and their links with other parts of the financial system. It examines the empirical data connected to all ETNs that are available globally, showing their features at the individual product and country level. The book merges the topic of ETNs with the ubiquitous trend in the contemporary investing industry - the increased focus on sustainability and ESG issues. It addresses the sustainability compliance of ETNs and their possible utilization in ESG investing, highlighting selected examples as case studies. Their strengths and weaknesses are underscored in this context by comparing them with other solutions and the legal frameworks in the countries in which they are listed. The book will interest the academic community and a broad range of practitioners, such as retail and institutional investors or asset managers"-- Provided by publisher.
Keywords: Exchange traded funds.; Investments -- Environmental aspects.; elektronické knihy; electronic books